Management of children with danger signs in integrated community case management care in rural southwestern Uganda (2014–2018) - Matte, Michael; Ntaro, Moses; Kenney, Jessica; Patel, Palka; Wesuta, Andrew Christopher; Kawungezi, Peter Chris; Bwambale, Shem; Ayebare, David; Baguma, Stephen; Bagenda, Fred; Miller, James S.; Stone, Geren; et al. (International Health, 2023)
Background: In integrated community case management (iCCM) care, community health workers (CHWs) pro- vide home-based management of fever, diarrhea and fast breathing for children aged < 5 y. The iCCM protocol recommends that children with danger signs for severe illness are referred by CHWs to health facilities within their catchment area. This study examines the management of danger signs by CHWs implementing iCCM in a rural context. Methods: A retrospective observational study that examined clinical records for all patients with danger signs evaluated by CHWs from March 2014 to December 2018 was conducted. Results: In total, 229 children aged < 5 y had been recorded as having a danger sign during 2014–2018. Of these children, 56% were males with a mean age of 25 (SD 16.9) mo, among whom 78% were referred by the CHWs as per the iCCM protocol. The age category of 12 to 35 mo had the highest numbers of prereferred and referred cases (54% and 46%, respectively). Conclusions: CHWs play a key role in early symptomatic detection, prereferral treatment and early referral of children aged < 5 y. Danger signs among children aged < 5 y, if left untreated, can result in death. A high proportion of the children with danger signs were referred as per the iCCM protocol. Continuous CHW training is emphasized to reduce the number of referral cases that are missed. More studies need to focus on children aged 12–35 mo and why they are the most referred category. Policymakers should occasionally revise iCCM guidelines to detail the types of danger signs and how CHWs can address these.
Keywords: Bugoye Community Health Collaboration; Community Health Workers; Integrated Community Case Management; Uganda